Pyrrolizidines for direct air capture and CO2 conversion. Issue 7 (3rd January 2019) - Hanusch, Jan M.; Kerschgens, Isabel P.; Huber, Florian; Neuburger, Markus; Gademann, Karl
Abstract : Scorpion-like designer amines enable fast, reversible, and efficient CO2 uptake from air. Abstract : Greenhouse gases such as CO2 strongly contribute to the rising temperatures of our planet, but as long as our society is dependent on fossil fuels, this trend will even increase in the near future. Therefore, CO2 capture and subsequent utilization constitute an approach for decarbonization and CO2 mitigation, and for this purpose, amine scrubbing remains the industrially most established process. In this article, we describe the CO2 capture-ability of pyrrolizidine-based diamines, a scaffold with remarkably good properties to fulfill this challenge. We observed fast equimolar CO2 -uptake, as well as high stability of these compounds during multiple capture and release-cycles. In addition, the amines could be utilized for direct air capture. Finally, we demonstrate the utility of the pyrrolizidine absorbents in the reduction of CO2 and for the formation of oxazolidinones.